2021
DOI: 10.3390/nu13041226
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Polyunsaturated Fatty Acids Supplementation in the Treatment of Attention Deficit Hyperactivity Disorder (ADHD) in Children and Adolescents: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Based on epidemiological and animal studies, the rationale for using polyunsaturated fatty acids (PUFAs) as a treatment for Attention Deficit Hyperactivity Disorder (ADHD) seems promising. Here, the objective was to systematically identify and critically assess the evidence from clinical trials. The primary outcome was ADHD core symptoms. The secondary outcomes were behavioral difficulties, quality of life, and side effects. We performed a systematic search in Medline, Embase, Cinahl, PsycInfo, and the Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
2
22
0
1
Order By: Relevance
“…n -3 PUFA supplementation showed efficacy in improving omission and commission errors, but not memory and information processing, in children with ADHD. On the other hand, Händel et al [ 74 ], in their 2021 systematic review and meta-analysis, with a total of 31 relevant RCTs including 1755 patients, found that PUFA supplementation showed no effect on ADHD core symptoms rated by parents (k = 23; SMD: −0.17; 95% CI: −0.32, −0.02) or teachers (k = 10; SMD: −0.06; 95% CI: −0.31, 0.19). There was no effect on behavioral difficulties rated by parents (k = 7; SMD: −0.02; 95% CI: −0.17, 0.14) or teachers (k = 5; SMD: −0.04; 95% CI: −0.35, 0.26), and there was no effect on quality of life (SMD: 0.01; 95% CI: −0.29, 0.31).…”
Section: Nutritional and Dietary Interventionsmentioning
confidence: 99%
“…n -3 PUFA supplementation showed efficacy in improving omission and commission errors, but not memory and information processing, in children with ADHD. On the other hand, Händel et al [ 74 ], in their 2021 systematic review and meta-analysis, with a total of 31 relevant RCTs including 1755 patients, found that PUFA supplementation showed no effect on ADHD core symptoms rated by parents (k = 23; SMD: −0.17; 95% CI: −0.32, −0.02) or teachers (k = 10; SMD: −0.06; 95% CI: −0.31, 0.19). There was no effect on behavioral difficulties rated by parents (k = 7; SMD: −0.02; 95% CI: −0.17, 0.14) or teachers (k = 5; SMD: −0.04; 95% CI: −0.35, 0.26), and there was no effect on quality of life (SMD: 0.01; 95% CI: −0.29, 0.31).…”
Section: Nutritional and Dietary Interventionsmentioning
confidence: 99%
“…The systematic review of Händel et al was centered around assessing the contribution of using polyunsaturated fatty acids (PUFAs, concretely omega 3 and omega 6) in the treatment plans of ADHD children and adolescents, obtained from randomized clinical trials [9]. Based on a substantial body of evidence, this review concluded that the benefits of PUFAs were not clear on core symptoms of ADHD reported by parents and teachers, neither were they clear on other behavioral measures nor on quality of life measures.…”
Section: Diet Intervention On Adhdmentioning
confidence: 99%
“…The methodology used in the Danish Health Authority guideline development has previously been described [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In short, the methodology is based on the recommendations for conducting systematic reviews and meta-analyses from the Cochrane Handbook for systematic reviews [ 8 ].…”
Section: Introductionmentioning
confidence: 99%